Pengenalan Kemampuan Membaca Al-Qur’an pada Anak Usia 5-6 Tahun Melalui Metode Ummi di TK Darul Ubur - Siti Sumiah; Nurul Fauziah; Yuwan Fijar Anugrah (Universitas 45 Surabaya, 2025)
The ability to read the Qur'an for children is the basis for themselves or to be conveyed to others, therefore efforts to improve the ability to read the Qur'an are urgent guidance for Muslims in order to improve, appreciate and practice the Qur'an in everyday life. One way of learning language for PAUD children is through the introduction of hijaiyah letters. Language learning for children starts from first identifying the child's abilities, whether the child understands and recognizes the hijaiyah letters. Letters arranged in written form need to be introduced to children to help children's reading process become smoother. The Ummi method is a method of reading the Koran that directly includes and practices tartil reading according to the rules of tajwid science. The Ummi method aims to meet the needs of schools or institutions in managing the Al-Qur'an learning sistem whose management is able to provide guarantees that ensure every student can read the Al-Qur'an in tartil when they graduate from school.